A Sociotechnical Framework for Semantic Biomedical Content Authoring and Publishing - Steve Fonin Mbouadeu; Asim Abbas; Fazel Keshtkar; Iram Wajahat; Syed Ahmad Chan Bukhari (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Due to the ubiquity of unstructured biomedical data, significant obstacles still remain in achieving accurate and fast access to online biomedical content. In lieu of the growing volume of biomedical content on the web, embedding semantic annotations has become key to enhancing search engine context-aware indexing, thereby improving search speeds and retrieval accuracy. We introduce Semantically: a socio-technical framework for semantic biomedical content authoring and publishing. Identifying the appropriate semantic vocabulary for biomedical content annotation is a time-consuming and technically challenging process. Semantically automates this search by recommending highly accurate annotations from a wide range of biomedical ontologies. Furthermore, the framework is integrated with a knowledge-sharing system which allows biomedical authors to collaborate on identifying precise annotations during the content authoring process. Similarly, preserving content-level semantics during and after publishing to foster semantic search remains a research challenge. Semantically addresses this barrier by extending Schema.org, a community-agreed and research engine endorsed guideline for publishing structured content on the web. gosemantically.com